Metastatic cervical lymphadenopathy masquerading as extrapulmonary tuberculosis (2012)
Introduction: Cervical lymphadenopathy can be due to various pathologies especially in the young. A high index of suspicion is required in the management of cervical lymphadenopathy to prevent misdiagnosis and wrong treatment. Case report: Here present the diagnostic challenge in the case of a young lady with nasopharyngeal carcinoma who initially presented solely with cervical lymphadenopathy. Previous fine needle aspiration cytology had suggested tuberculosis (TB) and she was commenced on anti-TB drugs. However failure of improvement and worsening symptoms led to another review in ENT clinic. A subsequent nasopharyngeal biopsy confirmed nasopharyngeal carcinoma. She subsequently improved after commencement of appropriate treatment. Conclusion: In regions with a high prevalence rate of tuberculosis, care must be taken to exclude malignancy in patients with cervical lymphadenopathy even when cytology suggests a granulomatous infection